Climatic stress increases forest fire severity across the western United States. (22nd July 2013) - van Mantgem, Phillip J.; Nesmith, Jonathan C. B.; Keifer, MaryBeth; Knapp, Eric E.; Flint, Alan; Flint, Lorriane
Abstract: Pervasive warming can lead to chronic stress on forest trees, which may contribute to mortality resulting from fire‐caused injuries. Longitudinal analyses of forest plots from across the western US show that high pre‐fire climatic water deficit was related to increased post‐fire tree mortality probabilities. This relationship between climate and fire was present after accounting for fire defences and injuries, and appeared to influence the effects of crown and stem injuries. Climate and fire interactions did not vary substantially across geographical regions, major genera and tree sizes. Our findings support recent physiological evidence showing that both drought and heating from fire can impair xylem conductivity. Warming trends have been linked to increasing probabilities of severe fire weather and fire spread; our results suggest that warming may also increase forest fire severity (the number of trees killed) independent of fire intensity (the amount of heat released during a fire).